Targeting complement activation in brain-dead donors improves renal function after transplantation. - Damman, J; Hoeger, S; Boneschansker, L; Theruvath, A; Waldherr, R; Leuvenink, H; Ploeg, R; Yard, B; Seelen, M (2011)
Kidneys recovered from brain-dead donors have inferior outcomes after transplantation compared to kidneys from living donors. Since complement activation plays an important role in renal transplant related injury, targeting complement activation in brain-dead donors might improve renal function after transplantation. Brain death (BD) was induced in Fisher rats by inflation of an epidurally placed balloon catheter and ventilated for 6h. BD animals were treated with soluble complement receptor 1 (sCR1) 1h before or 1h after BD. Kidney transplantation was performed and 7 days after transplantation animals were sacrificed. Plasma creatinine and urea were measured at days 0, 1, 3, 5 and 7 after transplantation. Renal function was significantly better at day 1 after transplantation in recipients receiving a sCR1 pre-treated donor kidney compared to recipients of a non-treated donor graft. Also treatment with sCR1, 1h after the diagnosis of BD, resulted in a better renal function after transplantation. Gene expression of IL-6, IL-1beta and TGF-beta were significantly lower in renal allografts recovered from treated donors. This study shows that targeting complement activation, during BD in the donor, leads to an improved renal function after transplantation in the recipient.